Stylistic category of accentuation in art texts (Eurasian Journal of Philology Science and Education, 2019)
This article addresses the concept of style and stylistic categories. In particular, it describes the stylisticcategory of accentuation. Stylistic accentuationcategories are found in all functional styles. Their functionsin every style are considered. However, in the study and analysis of the stylistic accentuationcategories, ithas become known that they exist in art texts as well. The stylistic categories of accentuation are conveyednot only through such linguistic unitsas intonation, word combinations, and sentences,but also throughparagraphs and dialogues. Afterwards they turn into aphorisms. By analyzing works of art, the role of thestylistic category of accentuation and its importance in the text creation have become known.